A Methodology for Simulation and Verification of Tool Path Data for 3-Axis and 5-Axis CNC Machining - Singh, Vishaldeep (My University, 2014)
A lot of research has been going on in the field of simulation of the tool path. The verification of the tool path using simulator is fast process as compared to the traditional method and this is what forms the focus of research. The dissertation is focused on the development of MACRO in SolidWorks environment for the simulation of tool path data for 3-axis and 5-axis machining. A CAD environment can be programmed using API for CAD automation. The tool path data is generated from the STL file of the original part. The work involves the simulation and verification of the tool path generated. The tool path generated is simulated using the Boolean approach for which a macro for 3-axis and 5-axis tool positioning has been developed. The output of the Boolean operation from the simulator environment has been saved in STL format for easy comparison with the original part. Two different parts were used to verify the results. The tool path is generated for these two parts and the data thus generated is simulated using the methodology discussed in the dissertation. The results are discussed for the given parts are discussed in chapter 6. The methodology works well for 3-axis and 5-axis machining. The ultimate aim of the present work is to develop the simulator using CAD environment and verify the results generated from the simulator and validate the results using Ray tracing method to prove that the output generated from the simulator is valid.
ME-CAD/CAM-Dissertation
Keywords: Simulation of NC Toolpath Data; 3-axis and 5-axis NC Toolpath; CNC Machining